Abatement of GHG emissions onboard mobile offshore units. Issue 1 (1st July 2022) - Ng, Chunwee; Li, Jizhao; Mishra, Rakesh; Fagan, Conn
Abstract: The International Maritime Organisation (IMO) is setting clear and ambitious goals for the decarbonisation of the shipping industry through the introduction of new regulations like the Energy Efficiency Design Index (EEDI), Energy Efficiency Existing Ship Index (EEXI) and Carbon Intensity Indicator (CII). However, these new regulations do not cover mobile offshore units like the Floating Production Storage and Offloading (FPSO) units that fall under the same maritime regime. To embrace sustainability in their corporate strategies and improve their public image, it is in the interest of existing oil and gas companies and operators to embark on a program of abating Greenhouse Gas (GHG) emissions through careful measurement and analysis. This paper is aimed at providing an overview of the typical FPSO's GHG emissions that originates from sources such as power generation, flaring, leakages and tank venting. The paper goes in-depth concerning some potential abatement measures that can be taken to reduce such emissions. This is followed by a case study of an FPSO assessed for the voluntary DNV class notation, Abate, to discuss how a competent third-party like DNV can play a significant role in helping offshore oil and gas companies demonstrate and achieve abatement in GHG emissions from their assets.